Birth cohort effects on maternal and child environmental health: a systematic review - JungMi Chae; Hyun Kyoung Kim (Korean Society of Women Health Nursing, 2021)
Purpose This study aimed to review recent findings from birth cohort studies on maternal and child environmental health. Methods Birth cohort studies regarding environmental health outcomes for mothers and their children were investigated through a systematic review. A literature search was conducted in PubMed, CINAHL, the Cochrane Library, Embase, and RISS to identify published studies using the keywords using a combination of the following keywords: maternal exposure, environmental exposure, health, cohort, and birth cohort. Articles were searched and a quality appraisal using the Newcastle-Ottawa Scale for cohort studies was done. Results A review of the 14 selected studies revealed that prenatal and early life exposure to environmental pollutants had negative impacts on physical, cognitive, and behavioral development among mothers and children up to 12 years later. Environmental pollutants included endocrine disruptors, air pollution (e.g., particulate matter), and heavy metals. Conclusion This systematic review demonstrated that exposure to environmental pollutants negatively influences maternal and children's environmental health outcomes from pregnancy to the early years of life. Therefore, maternal health care professionals should take steps to reduce mothers' and children's exposure to environmental pollutants.